Transparency and Firm Performance: The Influence of Earnings Quality and CSR under Dividend Policy Moderation - Siti Noer Afifah; Dyah Febriantina Istiqomah (Jurnal Akuntansi, 2026)
The market value of a business organization depends on the evaluation made regarding the performance and potential of the entity, which includes quantitative factors as well as qualitative aspects. This study focuses on the effect of earnings quality and corporate social responsibility (CSR) on firm valuation, more specifically analyzing the role of dividend policy as a moderator of these links. The target population is composed of firms that operate in the energy, basic materials, logistics, manufacturing, and infrastructural industries and are listed at the Indonesia Stock Exchange during the period of 2021 to 2024. The sample is purposefully chosen based on panel data and moderation analyses. Moreover, dividend strategy acts as a key factor in modifying the path and strength of these connections. These results suggest that firm wealth is not only shaped by fiscal performance, but also by how organizations align social commitments and strategic profit distributions.